RESULTS OF CARE OF PATIENTS AFTER COLORECTAL CANCER SURGERY AND SOME RELATED FACTORS AT CAN THO CITY HOSPITALS (Vietnam Journal of Community Medicine, 2021)
A prospective descriptive study was carried out at hospitals in Can Tho city from November 2020 to June 2021 on 168 patients after colorectal cancer surgery. Objectives: (1) Describe the characteristics of patients after colorectal cancer surgery at hospitals in Can Tho city (2) Find out the results of patient care and some related factors. Results: The mean postoperative hospital stay is 8.67 ± 2.55 days. Patients with severe pain on day 1 accounted for 8.3%, from day 3 no severe pain (0.0%), moderate pain accounted for 32.1%, mild pain increased to 67.9%. By day 7, moderate pain accounted for 24.4% and mild pain increased to 75.6%. Complications of incisional bleeding accounted for 1.2%, wound infection accounted for 4.2%, fluid leakage accounted for 1.8% and anastomosis accounted for 1.8%. Regarding care activities: incision care once a day accounted for a high rate of 89.9% and incision care not prescribed by a doctor accounted for 10.1%. Drainage care > 1 time/day accounted for 88.0% and drain care ≤ 1 time/day accounted for 12.0%. The results showed that there was a difference and statistically significant between patients with cardiovascular disease, digestive, endocrine with the outcome of care (p < 0.05), between wound infection and wound infection surgery, oral surgery was associated with the outcome of care (p < 0.05), between the patient's stay in hospital ≤ 1 week and > 1 week with the outcome of care (p < 0.05).
Keywords: Colorectal cancer care outcomes, colorectal cancer surgery.